REFORMULASI HADHANAH KEPADA ORANG TUA IBU PERSPEKTIF IMAM SYAFI’I - Qurrotul Aini, Hasyinah Romzah Kamilah (Mabahits : Jurnal Hukum Keluarga Islam, 2022)
When parents divorce, the child becomes one of the victims of the divorce, so special attention is needed in their upbringing. If in the divorce process there is a dispute in his care (hadhanah) then Syafi'i requires that the care be delegated to his mother. The reality of society, most mothers who are unable to care for their children do not only delegate care to their mothers. This research is library research and uses research library analysis. The primary data source in this study is the book of Al-Umm by Imam Asy-Syafi'i. This study concludes that: (1) When the mother is unable to take care of the child or remarries, the priority in the transfer of hadhanah is the grandmother (mother of the mother). And the care for grandmother will fall when the mother is able to return or is divorced from her new husband. (2) Imam Shafi'i's opinion is relevant to the current condition of society. Because the mother is hindered in child care, the right of care is transferred to the mother of the mother. Because the mother of the mother is considered to meet the requirements as hadhin and is considered to have more affection and attention to children.